Oxidation of polyacrylonitrile nanofiber webs as a precursor for carbon nanofiber: aligned and non-aligned nanofibers - Ismar, Ezgi; Sarac, A. Sezai (Springer Science and Business Media LLC, 2017)
Carbon nanofibers have a great potential for supercapacitor, battery, photocatalytic applications, and supporting material for light weight composite structures. In addition to use as a carbon fiber precursor, oxidized PAN nanofiber can also be used to produce inherently flame-resistant materials. Temperature and time are the major parameters for oxidation stabilization process and it is possible to examine the oxidation efficiency comparing with the Fourier transform infrared spectroscopy-attenuated total reflection (FTIRATR) spectroscopic results for different temperatures and time intervals. Thus, PAN nanofiber production and oxidation process well examined to fabricate desired featured CNFs. The conventional carbon fiber route which includes oxidation and carbonization can be adapted to obtain carbon nanofibers. In this study, several production parameters for PAN-based nanofiber fabrication were investigated intensely and oxidation studies of PAN-based nanofibers were examined to get an approach to oxidation procedure for carbon nanofiber production. Improved quality of precursor of PAN-based nanofiber webs directly affects the final product, carbon nanofiber properties. Thus, PAN-based nanofiber webs were prepared via electrospinning technique with aligned and non-aligned forms. Rotating and fixed collectors were used to diversify the samples and investigate the physical and chemical changes on the samples. FTIRATR spectroscopy was used to record the characteristic peaks of the nanofiber webs before and after oxidation. Nanofiber webs were characterized using DMA for their mechanical properties. Differential scanning calorimeter was used for thermal analysis. During the thermal treatment, nitrile group of PAN converts to C=N and C–N groups through cyclized structure. For all steps, surface morphology of the fibers was observed with scanning electron microscope and average fiber diameter was calculated through the fabrication steps. In this study, not only mechanical properties of the webs were investigated, but also chemical structure of the oxidized webs was studied. Aligned nanofibers have exhibited superior mechanical properties than the non-aligned ones.